2004
DOI: 10.3808/jei.200400024
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spatial and Vertical Heterogeneity of Grasslands Using Remote Sensing Techniques

Abstract: Grassland heterogeneity, defined by its components of spatial pattern, vertical structure, and species composition, is one of the most important indicators of prairie habitat. Maintaining grassland under conservation without disturbance may result in homogeneity at multiple spatial scales that could reduce wildlife diversity as a consequence. Therefore, monitoring grassland conditions that contribute to diversity can be critical for wildlife habitat and ecological integrity. Remote sensing, with multi-spatial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Considerable research has been conducted in GNP. Using remote sensing techniques, C 4 species cover [11], biophysical parameters [12,13] and spatial and vertical heterogeneity [2,14], as well as CO 2 exchange rate [15] have been estimated. These studies have shown the promise of using satellite imagery to study vegetation in GNP.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been conducted in GNP. Using remote sensing techniques, C 4 species cover [11], biophysical parameters [12,13] and spatial and vertical heterogeneity [2,14], as well as CO 2 exchange rate [15] have been estimated. These studies have shown the promise of using satellite imagery to study vegetation in GNP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the functional role of grasslands (nitrogen and carbon storage) changes with agricultural practices and this affects environmental behavior. 9,10 Yet, monitoring grassland management with remote sensing is still limited both by the low revisit frequency of high spatial resolution sensors and the low spatial resolution of high revisit frequency sensors. 5,6 In this context, the identification of agricultural practices on grassland in farming systems, such as grazing and mowing, is of prime importance for environmental protection and sustainable agriculture.…”
Section: Identification Of Grassland Practices: Interests Of Remote Smentioning
confidence: 99%
“…Obtaining better correlations of species use patterns within a biotope may require the use of higher resolution imagery, or techniques such as spectral (textural) analysis (e.g., Guo et al 2004;Bellis et al 2008) or LiDAR (Vierling et al 2008;Goetz et al 2010) that provide an alternate means of quantifying internal heterogeneity. Recall also that even if higher resolution imagery is viewed by the researcher at too small a mapping scale (i.e., not at the scale viewed by the organism), it still may be difficult for the researcher to discern this heterogeneity and thus to appreciate its potential influence on the species.…”
Section: Matching Both Spatial and Temporal Scales Of Explanatory Varmentioning
confidence: 99%